Situational analysis on the recovery of patients who have undergone major abdominal surgery - Warawan Udomkhwamsuk (2020)
© 2020 The Authors. Nursing Open published by John Wiley & Sons Ltd Aim: To analyse the recovery situation of patients who underwent abdominal surgery. Design: A descriptive study. Method: This study was conducted among 50 participants: 15 postoperative patients, 16 caregivers, 2 surgeons and 17 nurses in a tertiary hospital in Thailand. The state of patients’ recovery after undergoing major abdominal surgery was analysed using Donabedian's approach. Results: The findings showed that hospitals and some organizations do not have a clear policy about clinical care to help patients recover after undergoing major surgery or to prevent the risk of complications following major abdominal surgery. In addition, there were no clinical practice guidelines in use in each ward. Each ward should have a set of guidelines and procedures for assisting with patient recovery. The procedures should be based on nursing care. It is necessary to have a coordinated multidisciplinary care guideline to use with other health professionals to promote the recovery of patients.